Insuring consumption and happiness through religious organizations - Dehejia, Rajeev H.; DeLeire, Thomas C.; Luttmer, Erzo F. P. (National Bureau of Economic Research, 2005)
"This paper examines whether involvement with religious organizations insures an individual's stream of consumption and of happiness. Using data from the Consumer Expenditure Survey (CEX), we examine whether households who contribute to a religious organization are able to insure their consumption stream against income shocks and find strong insurance effects for whites. Using the National Survey of Families and Households (NSFH), we examine whether individuals who attend religious services are able to insure their stream of happiness against income shocks and find strong happiness insurance effects for blacks but smaller effects for whites. Overall, our results are consistent with the view that religion provides an alternative form of insurance for both whites and blacks though the mechanism by which religious organizations provide insurance to each of these groups appears to be different"--National Bureau of Economic Research web site.
Keywords: Schwarze. USA; African Americans -- Religion -- Economic aspects; Public worship -- Economic aspects -- United States; Religions -- Economic aspects -- United States; Whites -- United States -- Religion -- Economic aspects; USA